USING INTERNET SOURCES IN TEACHING ECONOMIC SUBJECTS - Svetlana V. Kulikova; Nataliya A. Kameneva (Высшее образование в России)
This paper examines the possibility of increasing the efficiency of the learning process by using economic and scientific information sources. The authors demonstrate that for improving the quality of higher education it is necessary to use Internet resources that have been previously assessed by the experts. Open information resources should be grouped and classified according to certain criteria. Such an approach enables not to take much time to search for sources of employment information at lectures and seminars. Orientation on formation of necessary information competencies among the students is also shown.